Optimizing the Solar Cell Front Side Metallization and the Cell Interconnection for High Module Power Output. (August 2016) - Witteck, Robert; Schulte-Huxel, Henning; Holst, Hendrik; Hinken, David; Vogt, Malte; Blankemeyer, Susanne; Köntges, Marc; Bothe, Karsten; Brendel, Rolf
Abstract: Improving the light trapping in a module results in an increase in the generated current. Consequently, an optimization of the front grid metallization of the cell is required for the best trade-off between series resistance, shading, and recombination losses. For this purpose, we combine ray tracing and electrical solar cell and module calculations that explicitly account for cell and module interactions. Our model bases on experimentally verified input parameters: We determine the electrical and optical properties of the front metal fingers of passivated emitter and rear cells (PERC). We show that the effective optical width of the front metal fingers in the module is significantly reduced by 54%. The optimized simulated module has 120 half-size PERC with 20.2% cell efficiency and has an output power of 295.2 W. This is achieved with an increased number of 120 front metal fingers per cell, four white-colored cell interconnection ribbons (CIR), and an increased cell spacing. Applying these optimized design changes to an experimental module we measure a module power output of 294.8 W and a cell-to-module (CTM) factor of 1.02. Measured and simulated power agree and the deviations in V oc, I sc and FF are less than 0.91%rel . We perform a module power gain analysis for the fabricated module and simulate a potential maximum module power of 374.1 W when including further improvements.